Livestock breeding in Omsk region in second half of the 1960’s till first half of the 1980’s: trends and outcomes - D. S. Orlov (Омский научный вестник: Серия "Общество. История. Современность")
The evolution of the basic livestock breeding sectors (meat and dairy cattle breeding, pig breeding, poultry farming, sheep breeding) in the Omsk Region in the 1960's – the first half of the 1980's is reconstructed, and their trends and outcomes are determined. It is proved that in the second half of the 1970's, the pace of development of agricultural production in the region declined, and in the early 1980's recession was recorded. At the same time, stagnation in the agrocomplex of the region was combined with positive structural changes. In gross production the share of animal husbandry grew. Within its framework, the role of early-ripening cattle-breeding sub-sectors — poultry and pig-breeding — has regularly increased. The intensive increase in livestock production in the first half of the period under review was a consequence of the recovery of the industry after the crisis of the early 1960's, and the positive impact of measures taken at the March (1965) plenum of the Central Committee of the CPSU. The slowdown in the development of the industry took place in the second half of the 1970's, and in 1980–1982